Collective rights in the framework of public international law and other considerations, preliminary reflections - González-Olaechea Franco, Javier (2022)
In the framework of public international law, the collective rights recognized and protected by the ILO Convention No. 169 on indigenous and tribal peoples (1969) are considered human rights. Considering that law and reality constantly feed each other, even more so in the emerging disruptive era, multiculturalism and interculturality, the rights approach, international protection systems and public international law allow to offer preliminary reflections that underline these relationships in the progressive recognition of the Convention as part of international human rights law.